Continuous noise covert transmission scheme based on QCSK - Ying HUANG; Zehan WAN; Jing LEI; Ke LAI (Tongxin xuebao)
The existing embedded scheme requires far lower transmission power of the covert system than that of the host system, and thus decreasing the reliability of covert transmission.To figure out the above limitations, a continuous noise covert communication scheme based on quadrature chaos shift keying (QCSK) was proposed.The QCSK signal containing covert information and artificial noise were transmitted alternately, and the illegal energy detection was effectively resisted by the continuity of noise which has strong concealment in both time and frequency domains.Furthermore, extremely low power was not required to meet the demand of convert communication in QCSK, whereas allowing the increase of transmit power under the condition that the performance of the host system to improve the performance of covert transmission.Theoretical analysis and simulation results show that the bit error rate (BER) of covert transmission brings two orders of magnitude improvement compared with the existing scheme at BER=1×10-7 for host system.